A solving-reprecipitation theory for self-healing functionality of stannate coating with a high environmental stability. (20th August 2015) - Yang, Na; Li, Qing; Chen, Funan; Cai, Peng; Tan, Cui; Xi, Zhongxian
Abstract: A superhydrophobic stannate coating with self-healing functionality was fabricated on surface of AZ91D magnesium. The hierarchical micro-nano structure was created through two steps, an acid corrosive process and deposition of stannate. The coating was modified with stearic acid after 4 h self-healing process, a superhydrophobic surface was obtained with a water contact angle as high as 157.8° and a slide angle as low as 3°. In this report, we proposed a solving-reprecipitation theory for explainning the self-healing mechanism based on ionic strength. Corrosion performance of superhydrophobic surface was studied by using potentiodynamic polarization in neutural 3.5 wt.% NaCl solutions and stimulated acid rain with different pH value. It exhibited fine corrosion resistance even in stimulated acid rain with pH value of 2.5. The acid rain dropping test, chemical stability and long-term stability test indicated that suyperhydrophobic surface can be remained superhydrophobility after dropping 1000 mL acid rain, during the pH value ranging from 1 to 14 or even exposuring in the evironment as long as 16 weeks. This paper provide a new theory for stannate self-healing process and also expand application scope of superhydrophobic materials.